Commentary - Perkins, Henry S. (Cambridge quarterly of healthcare ethics, 2000)
Many people see high income as the primary motivation of today's American physicians. But in “The Culture of Physician Autonomy, 1900 to Present,” Dr. Pont offers a provocative new idea: that preserving professional autonomy has been a far more powerful motivation through this century.